Актуальные теплофизические проблемы управления ресурсом ядерных энергоблоков АЭС - Носовский, А.В.; Шараевский, И.Г.; Фиалко, Н.М.; Зимин, Л.Б.; Шараевский, Г.И. (Проблеми безпеки атомних електростанцій і Чорнобиля, 2017)
Представлены результаты комплексного анализа нерешенных теплофизических проблем управления ресурсом ядерных энергоблоков АЭС с водо-водяными реакторами типа ВВЭР. Определены актуальные направления качественного совершенствования систем диагностики и прогноза реального технического состояния элементов и систем ядерных реакторов с целью обеспечения возможности продления их ресурса. Рассмотрен комплекс определяющих физических, технических и диагностических факторов, подлежащих учету при разработке нового поколения диагностических систем для раннего автоматического обнаружения начальных фаз потенциально опасных отклонений параметров теплогидравлических режимов активных зон от регламентируемых значений. Наведено результати комплексного аналізу невирішених теплофізичних проблем керування ресурсом ядерних енергоблоків АЕС із водо-водяними реакторами типу ВВЕР. Визначено актуальні напрямки якісного удосконалення систем діагностики та прогнозу реального технічного стану елементів і систем ядерних реакторів з метою забезпечення можливості подовження їхнього ресурсу. Розглянуто комплекс визначальних фізичних, технічних та діагностичних факторів, що підлягають урахуванню під час розробки нового покоління діагностичних систем для раннього автоматичного виявлення початкових фаз потенційно небезпечних відхилень параметрів теплогідравлічних режимів активних зон від регламентованих значень The results of a comprehensive analysis of unresolved thermal problems of resource management nuclear NPP with water-cooled VVER reactors. Identified current trends in the qualitative improvement of diagnostics and forecasting technical condition of the real elements and nuclear reactor systems in order to ensure the possibility of extending their life. Thermophysical aspects of physical processes that are capable of initiating potentially damaging defects to their elements and systems during the operation of the main energy types reactor installations are considered. Particular attention is paid to the causes of the emergence and development of latent damage in critical elements of the primary circuit critical to the safety of nuclear power plants. The features and the calculation methodology of the corresponding thermohydrodynamic and vibrational processes are analyzed, as well as the principal aspects of the main approaches to early automatic detection of the conditions of nucleation and subsequent development of anomalous and pre-emergency operational states in the elements and systems of active zones and heat exchange equipment of the first circuit of reactor plants. The complex of determining the physical, technical and diagnostic factors to be considered when developing a new generation of diagnostic systems for early automatic detection of the initial phases of potentially dangerous deviations of active zones heat-hydraulic modes parameters from regulated values.